The Implementation of School Based Management in MTs. Islamiyah Ypi Batang Kuis - Aldin Damanik; Ahmad Husin Siregar (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to reveal how the pattern of implementation of school-based management (SBM) in Islamic MTs YPI Batang Quiz. This research uses a qualitative approach. Or collected from informants who are selected in a strict way. Research data were collected by interview, observation and documentation study techniques. Data were analyzed using the miles and Hubberman steps. The results of the study revealed that: Planning and implementing patterns of implementation of school-based management (SBM) in MTs YPI Batang Quiz has been relatively running well according to the format of school-based management. While the obstacles faced are not significant and can be resolved properly.